The profile of biology teaching and learning materials from scientific literacy perspective - Indah Karunia Sari; Yenny Anwar; Meilinda Meilinda (JPBIO (Jurnal Pendidikan Biologi), 2021)
Many researchers have developed scientific literacy, but no one has done scientific literacy study on biology teaching materials that include environmental change materials. The purpose of this study is to assess scientific literacy in senior high school biology teaching materials utilized by teachers in Palembang's Ilir Barat I district. This research was conducted using biology teaching materials in the form of books and modules used by teachers in grade X in 13 senior high schools in Ilir Barat I district, Palembang, both in public and private schools. This study employed a descriptive technique with content analysis, which included collecting and assessing biology teaching materials for senior high school grade X. All biology teaching materials for grade X of senior high school utilized in Ilir Barat I district Palembang were used as the population in this study, with environmental changes in biology teaching and learning materials for grade X of senior high school as the sample. The findings revealed that the scientific literacy category was represented in the teaching materials used in 13 senior high schools in the district of Ilir Barat 1 Palembang, with an average percentage of 34.24% for the body of knowledge, 45.35% for a method of investigation, 9.75% for a method of thinking, and 10.86% for the category of science, technology, and society interaction.